Climate and global environmental change [understanding global environmental change]. - Harvey, Danny (Harlow : Longman, 2000)
Climatic change, now more than ever in this age of global warming, is seen as fundamental to the study of the environment. This text examines the importance of climate as one of the major forcing functions in the global environmental change process. It emphasizes both human-induced climatic change and natural climatic change, providing a comprehensive historical context and important projections for the future. It offers a thorough, up-to-date, critical overview of the physical science behind global warming concerns.
Includes bibliographies.
All age.
Keywords: Climatic changes